2015
DOI: 10.1190/tle34060684.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pressure response into a fractured zone of Precambrian basement to understand deep induced-earthquake hypocenters from shallow injection

Abstract: Analysis of the spatiotemporal distribution of seismic events in Youngstown, Ohio, from previous studies has revealed that the seismicity was triggered by injection during January through December 2011 into a brine-disposal well (North Star #1 well). Investigation of the hypocenters of induced earthquakes, which were substantially deeper than the injection zones in the well, brings the question of how pore pressure could migrate more than a kilometer below the injection zone into the Precambrian basement rock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Results of the hydromechanical modeling of enhanced oil recovery in northern Alberta showed that stress changes in the reservoir induced surface heave (varied from 4 to 18 cm at different sites) measured by geomechanics (Pearse et al, 2014). Elastic moduli (i.e., Young's modulus, Poisson's ratio, bulk modulus, shear modulus) and poroelastic constant (i.e., Biot coefficient) of the reservoir are constant inputs in the hydromechanical modeling to estimate, forecast and historymatch Earth surface uplift (Bjørnarå et al, 2018;Zheng et al, 2019;Raziperchikolaee and Pasumarti, 2020b) as well as other aspects of poroelastic responses including reservoir's stress path estimation (Vidal-Gilbert et al, 2010;Li and Laloui, 2016;Raziperchikolaee et al, 2019), fault activation prediction (Mazzoldi et al, 2012;Jha and Juanes, 2014;van et al, 2019), and induced seismicity (Raziperchikolaee and Miller, 2015). In this work, the changes in Biot coefficient and elastic moduli as a function of pore pressure and stress were reviewed using available experimental measurements for different rock types.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the hydromechanical modeling of enhanced oil recovery in northern Alberta showed that stress changes in the reservoir induced surface heave (varied from 4 to 18 cm at different sites) measured by geomechanics (Pearse et al, 2014). Elastic moduli (i.e., Young's modulus, Poisson's ratio, bulk modulus, shear modulus) and poroelastic constant (i.e., Biot coefficient) of the reservoir are constant inputs in the hydromechanical modeling to estimate, forecast and historymatch Earth surface uplift (Bjørnarå et al, 2018;Zheng et al, 2019;Raziperchikolaee and Pasumarti, 2020b) as well as other aspects of poroelastic responses including reservoir's stress path estimation (Vidal-Gilbert et al, 2010;Li and Laloui, 2016;Raziperchikolaee et al, 2019), fault activation prediction (Mazzoldi et al, 2012;Jha and Juanes, 2014;van et al, 2019), and induced seismicity (Raziperchikolaee and Miller, 2015). In this work, the changes in Biot coefficient and elastic moduli as a function of pore pressure and stress were reviewed using available experimental measurements for different rock types.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the developing characteristics of an interconnected fracture zone have been extensively investigated (Duboeuf et al., 2017; Huang et al., 2018; Ma et al., 2020; Ning et al., 2019; Raziperchikolaee and Miller, 2015). The property and combination type of overburden, coal seam-mining thickness, width of extraction, and advancing speed are known to substantially impact the height of an interconnected fracture zone (HIFZ).…”
Section: Introductionmentioning
confidence: 99%